PENYULUHAN KUNJUNGAN ANTENATAL CARE (ANC) DI DESA SALO TIMUR - Rizki Rahmawati Lestari; Ade Dita Puteri; Zurrahmi Z.R (COVIT (Community Service of Health), 2021)
The implementation method used in this activity is in the form of ANC counseling and discussions with participants. This activity took place at the Salo Timur Village Office Hall on December 11, 2020. The target of this activity was pregnant women in Salo Timur Village, the Salo Health Center Work Area. The media used to facilitate the implementation of counseling were using infocus and laptops where the extension material was in the form of Powerpoints, and the distribution of leaflets to the audience.Pregnancy examination is one of the important steps towards a healthy pregnancy and is something that pregnant women must do. Pregnancy checks can be done through a gynecologist or midwife with a minimum of 4 checks during pregnancy, namely in the first trimester of pregnancy, the second trimester and twice in the third trimester of pregnancy (applies in normal pregnancy).Antenatal Care (ANC) visit is a visit from a pregnant woman midwife or doctor as early as possible since she feels that she is pregnant to get antenatal care. At each ANC visit, the officer collects and analyzes data regarding the mother's condition through anamnesis and physical examination to obtain a diagnosis of intrauterine pregnancy, and whether there are any problems or complications. (Saifudin, et al, 2002).During the period of pregnancy, mothers are advised to undergo ANC examinations. ANC examination is a pregnancy check to optimize the mental and physical health of pregnant women. This examination aims to recognize early on if there are abnormalities or complications during pregnancy so that pregnant women can immediately take further steps. Not only that, ANC also aims to monitor the development of pregnancy, prepare for childbirth, prepare for exclusive breastfeeding and prepare mothers to accept the presence of a baby.